Rumah Belajar Sebagai Solusi Anak Terlantar Yang Putus Sekolah - Kanaya Ledy Adinda (Journal Innovation In Education, 2025)
The Learning House emerged as a response to the existing issues, particularly the large number of abandoned children who are either not attending school or have dropped out. This condition leaves them lacking the skills and abilities to develop their potential and talents. Therefore, the aim of this design is to provide a space and facilities that support the creativity development of abandoned children in terms of individual, social, talent, and potential aspects through various training programs. The planning and design process begins by applying the concept of children's creativity development as a solution to help them improve their skills, enhance their potential, and strengthen their ability to socialize with the community. The supporting factors in the implementation of the Learning House as a solution for abandoned children who have dropped out of school include community support, infrastructure assistance from the local government, and the motivation of these children to transform their lives, progress, and become independent.